Analisis Manajemen Risiko dalam Penggunaan mobile banking: Studi Kasus pada Bank Syariah di Indonesia. - Asrori, Moh. Nasukhin (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze risk management in the use of mobile banking at Islamic banks in Indonesia. The development of information technology has encouraged digital transformation in the banking sector, including mobile banking services that offer convenience and efficiency for customers. However, the use of this technology also raises various risks, such as technological risks (cybersecurity, system errors, and malware), operational risks (transaction errors and human errors), and risks to customer trust. This study uses a descriptive qualitative approach to identify these risks and analyze the mitigation efforts made by Islamic banks. The results show that effective risk management strategies, such as implementing data encryption, double authentication, HR training, and transparent communication with customers, are key to maintaining system security and increasing public trust. With good risk management, Islamic banks can maximize the potential of mobile banking while minimizing the negative impacts caused by digital risks.